On conditions of technical stability of solutions of a nonlinear boundary-value problem describing processes under parametric excitation in a Hilbert space - Matviichuk, K. S. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
Sufficient conditions for technical stability are obtained for solutions of a nonlinear boundary-value problem which describes distributed parametric processes in a Hilbert space.